Development of Cinchonine Emulgel as a Topical Antibacterial using Response Surface Methodology - Hariyanti Hariyanti; Uqie Shabrina Hasyyati; Shintia Lintang Charisma; Monika Wisda Herisman; Asmiyenti Djaliasrin Djalil; Aditya Singgih Raharjo; Salsabila Nasywa Artamevia; Rika Rakhmania; Afshana Awaliah Rahmadani (Jurnal Kefarmasian Indonesia, 2026)
Cinchonine has potential as a topical antibiotic with a mechanism of action that inhibits bacterial cell wall formation. Cinchonine is insoluble in water, resulting in poor penetration. The aim of the research was to develop a cinchonine emulgel formula using the Response Surface Method (D-optimal) as an antibacterial with parameters spreadability, adhesiveness, pH, and viscosity. The optimum cinchonine emulgel was determined based on the desirability value (range 0-1). The release test of cinchonine emulgel was carried out using a 12-14 kD cut-off dialysis bag. Cinchonine emulgel was tested for antibacterial activity against Pseudomonas aeruginosa and Staphylococcus aureus by the diffusion method with a positive control and a negative control. The inhibition zone parameters were carried out with observation intervals of 18 and 24 hours. Stability test of the optimum formula was carried out by cycling test and accelerated method with test parameters including spreadability, adhesiveness, and pH. The optimum composition of cinchonine emulgel consisted of cinchonine 1.5; HPMC 2; glycerin 1; tween 80 4.99; propylene glycol 1.14; oleic acid 14.84; and deionized water up to 100% with a desirability value: 0.504, spreadability: 3.92±0.38cm; adhesiveness: 2.17±0.29 second, pH: 4.72±0.11; and viscosity: 12050±900.39cP (p<0.05). The release of cinchonine emulgel was 19.25% controlled. Observation of inhibition zone at 18 and 24 hours respectively for cinchonine emulgel preparation against Pseudomonas aeruginosa was 7.68±0.14 and 6.50±0.37mm, Staphylococcus aureus was 10.47±0.37 and 10.36±0.69mm compared to control (gentamicin ointment: 18.15±0.90, and 16.99±1.61mm; blank control: 0.00±0.00, and 0.00±0.00mm). Cinchonine emulgel had good stability during short-term storage.